Endoparasites infecting the semiaquatic coral snake Micrurus surinamensis (Squamata: Elapidae) in the southern amazonian region, Mato Grosso state, Brazil - Avila, R. W.; Morais, D. H. [UNESP]; Anjos, L. A. [UNESP]; Almeida, W. O.; Silva, R. J. [UNESP] (Int Inst Ecology, 2013)
A parasitological survey was conducted in specimens of the semiaquatic coral snake Micrurus surinamensis, a poorly known South American elapid. Four specimens collected at the southern Amazon region in the Brazilian state of Mato Grosso were analyzed for endoparasites. Three parasite species were recovered from the snake hosts: the pentastomid Sebekia oxycephala, the nematode Physaloptera sp. and the trematode Opisthogonimus lecithonotus. This represents new locality and host record for S. oxycephala and O. lecithonotus.
Keywords: parasitism; Pentastomida; Nematoda; Trematoda; snakes